Granuloma annulare of the neckline. - Tagliavanti, M.; Pirrelli, M. (European Journal of Pediatric Dermatology, 2014)
Case report. A 69-year-old woman presented scarcely symptomatic, erythematous, circinate lesions of the neckline from a year. The family history did not show similar lesions in other members of the group; a sister was hypothyroid. The lesions started in the sternal region and then expanded to involve all the neckline without showing significant seasonal variation. After several months lesions appeared also on the root of the upper limbs up to the elbows. The physical examination revealed erythematous infiltrated annular lesions on the upper limbs (Fig. 2); on the neckline there were isolated papular lesions of about 1 cm and circinate lesions describing wavy lines intertwined with each other (Fig. 1). Undecided between the diagnosis of lymphocyte infiltration and granuloma annulare we performed a biopsy; the histology (Fig. 3) showed a tuberculoid granuloma with some giant cells and rare foci of necrobiosis of collagen, leading usto the final diagnosis of granuloma annulare.